ANALISIS FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT PADA PRODUK KREDIT UNION (CU) SEMARONG KECAMATAN TAYAN HILIR - Very, Xaverius; Aminuyati, Aminuyati; Okianna, Okianna (Universitas Tanjungpura, 2022)
AbstrackThis study aims to determine the analysis of public interest in CU Semarong products. The research method used is descriptive research in the form of qualitative research. The data sources of this study used data from interviews and observations, consisting of 5 respondents as CU members and 1 respondent as administrative staff. To test the validity of the research data, triangulation of sources and theories was carried out. Based on the tests conducted, this study shows that people's interest in saving is influenced by 2 significant factors, namely location and reputation factors. Close location, good road access, has a good name so that customers feel comfortable and safe in choosing savings products at the Semarong Tayan Hilir CU and the public's interest in choosing loan products at the Semarong Tayan downstream CU is influenced by 3 factors, namely Promotion, Product Knowledge, and Quality of Service. Promotions are carried out by distributing pamphlets/brochures, via the internet, and social media, spreading knowledge to the public so that it raises people's curiosity to find out more by visiting branch offices, the services they provide are also good, polite, courteous, thus attracting public interest. to borrow at CU Semarong.Keywords: Interests, Society, CU Semarong Products.